Implementation of Work Flexibility at BPMP North Maluku - Nahrudin M. Nur; Marwan; Abdul Rahman Jannang (LPPM STIE KRAKATAU, 2026)
This study examines how Work From Anywhere (WFA) implementation influences employee discipline and performance at Education Quality Assurance Center or locally Balai Penjaminan Mutu Pendidikan (BPMP) of North Maluku Province, addressing the limited empirical evidence on post-pandemic WFA practices in vertical government agencies. This qualitative descriptive study employed a phenomenological approach. Data were collected through interviews, observation, and documentation involving six purposively selected informants, consisting of the Head of BPMP and five WFA-implementing employees. Data analysis followed Miles and Huberman’s interactive model through coding, data reduction, triangulation, and conclusion drawing. WFA shows a conditional and dualistic effect: employees maintain regulatory compliance, obedience, and work responsibility, but attendance discipline declines without direct supervision, with 75% of employees recording late attendance in November 2025. Performance is sustained through Employee Performance Targets or locally Sasaran Kinerja Pegawai (SKP) systems and individual commitment rather than WFA flexibility itself. Organizational performance issues were attributed to budget efficiency constraints and weak regional government commitment rather than WFA implementation. The effectiveness of WFA in vertical government agencies depends on personal discipline, organizational readiness, digital monitoring, and an accountability-oriented work culture. This study is limited by six informants from a single agency, a short research period, and a qualitative design that does not measure causal relationships statistically. This study provides empirical insights into WFA implementation in Indonesia’s public sector, highlighting the need for accountability mechanisms to support flexible work policies and maintain service quality.